Molecular basis for the specific and multivariant recognitions of RNA substrates by human hnRNP A2/B1 - Baixing Wu (Nature Portfolio, 2018)
RNA-binding protein hnRNP A2/B1 is suggested to promote miRNA processing as a m6A 'reader'. Here, the authors determine crystal structures of RRM domains of hnRNP A2/B1 in complex with various RNA substrates and determine that hnRNP A2/B1 may function as an auxiliary factor in 'm6A switch' instead.